Returning home: psychosocial care during the re‐entry phase of cancer survivorship in rural Australia. (28th August 2014) - Pascal, J.; Johnson, N.; Dickson‐Swift, V.; Kenny, A.
<x xml:space="preserve">Abstract</x> The purpose of this research was to highlight gaps in formal psychosocial care for cancer survivors in rural communities. The study was conducted in rural Victoria, Australia, and involved interviews with people with various stages of cancer progression, cancer diagnoses and survival times, who were interviewed about their experiences of psychosocial cancer care. Interviews focused on their experience of psychosocial care and were audio‐recorded and transcribed verbatim. Data were thematically analysed to identify key themes. Findings demonstrate that psychosocial care is essentially informal within the re‐entry period after cancer diagnosis and treatment. Despite current Australian clinical guidelines on psychosocial care for people with cancer, which indicate the need for the provision of formal psychosocial care, participants in this study largely cared for themselves, or received informal support from family, friends and community members. Many psychosocial needs remained unmet and professional support was lacking. While this study was conducted in rural Australia, many of our findings have been echoed in studies from other countries. The findings have implications for treatment protocols and discharge planning, health professional–patient–family relationships, and the long‐term well‐being of cancer survivors living in rural communities. A model for understanding the experience of formal supportive care during the re‐entry phase of survivorship is proposed.